1993
DOI: 10.1002/ar.1092350305
|View full text |Cite
|
Sign up to set email alerts
|

Transport of casein submicelles and formation of secretion granules in the golgi apparatus of epithelial cells of the lactating mammary gland of the rat

Abstract: Lactating mammary glands fixed by perfusion with 5% glutaraldehyde subsequently were postfixed with potassium ferrocyanide reduced osmium or were treated with tannic acid. Stained thin sections were examined with the electron microscope and stereopairs were prepared. The distribution of casein submicelles was analyzed in the various components of the Golgi apparatus. The Golgi stacks were composed of five or six elements, all of which contained casein submicelles 20 nm in diameter. The cis-tubular network or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 30 publications
0
34
0
2
Order By: Relevance
“…Obviously, the trans Golgi cisternae and secretory vesicles are swollen and distended in lactating MECs (e.g. see Clermont et al, 1993). The substantial increase in lactose concentration in the milk from rats receiving the lipid-deprived diet could therefore result from the decrease in the volume of milk produced by these animals, coupled with the maintenance of lactose synthesis at high level.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the trans Golgi cisternae and secretory vesicles are swollen and distended in lactating MECs (e.g. see Clermont et al, 1993). The substantial increase in lactose concentration in the milk from rats receiving the lipid-deprived diet could therefore result from the decrease in the volume of milk produced by these animals, coupled with the maintenance of lactose synthesis at high level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in certain algae, large glycoprotein 'scales' are synthesized in the Golgi and then transported to the cell surface; these scales can be detected only within Golgi cisternae and never in the associated transport vesicles [I 3]. Similar observations were made with mammalian cells that transport lipoprotein particles, casein submicelles or virus particles through the Golgi stack [14][15][16]. Other studies indicated that Golgi enzymes are not segregated into precisely defined subcompartments, but instead form overlapping concentration gradients within the stack [17 -20].…”
Section: Introductionmentioning
confidence: 86%
“…For example, electron microscopy studies suggest that certain kinds of secretory cargo are absent from COPI vesicles, or are much less concentrated in these vesicles than in Golgi cisternae [13][14][15] (J. Bergeron, personal communication). However, some secretory proteins can be packaged into COPI vesicles [11,12,22,24].…”
Section: Transit Of Secretory Proteins Through the Golgi Stackmentioning
confidence: 99%
“…4B). Indeed, for large cargo aggregates, such as collagen, a number of EM studies seemed to provide evidence for these large aggregates remaining in cisternae as they traversed the Golgi stack (Bonfanti et al, 1998;Clermont et al, 1993;Melkonian et al, 1991;Mironov et al, 2001). Proof for the idea of (B) Cisternal-maturation model.…”
Section: Mechanisms Of Trafficking Through the Golgimentioning
confidence: 99%